Horizontal–vertical ratio for concrete pumping pipe - Ki-Yeol Kim; Young-Jin Kim; Myoung-Sung Choi (Case Studies in Construction Materials, 2022)
For the construction of high-rise building, a horizontal pipe pumping test is usually conducted and using obtained test results, vertical actual constructing condition could be evaluated. In this study, horizontal and vertical pumping experiments are performed under various mixing and construction conditions using rheology-based quantitative performance prediction technology to derive a horizontal–vertical ratio of concrete pumping pipe for evaluating concrete pumping performance. Computational fluid dynamics is used to analyze the correlation between experimental results and additional vertical lengths. Analysis results confirm that compressive strength and plastic viscosity correlate with vertical and horizontal correlation coefficients; the pipe length, flow rate, and yield stress have no significant effect on the correlation coefficient. Based on analysis result considering various factors, multiple regression analysis is performed to propose horizontal–vertical ratio relationship for the concrete pumping pipe.